Evaluasi Status Hara dan Rekomendasi Pemupukan Padi Sawah Di Kecamatan Batin III Ulu Kabupaten Bungo Jambi - Saidi, Busyra B (LPPM Universitas Jambi, 2022)
Evaluation of Nutrient Status and Recommendations for Fertilization of paddy rice. The assessment was carried out in Batin III Ulu District, Bungo Jambi Regency with a rice field area of 655 ha spread across 8 (eight) villages. This study aims to evaluate the nutrient status and determine fertilization recommendations in paddy rice. The study used a description method based on field observations and laboratory analysis. Examples of composite soils resulting from the field, analyzed the nutrient status of N, P, and K as well as soil pH with the Paddy Soil Test Kit. Based on the value of the N, P, K nutrient status test, it is determined to recommend fertilizer application. N fertilizer during the growth period is applied 3 (three) times, namely at planting time (before 14 DAP), without the use of LCC (leaf colour chart), the second fertilization on active tillering stadia (21-28 DAP), and the third on flower primordia stadia (50 days after planting). The results of the nutrient status analysis with STD, the P and K nutrient status of the soil are grouped into three classes, namely low, medium, and high. From the P and K status classes of the soil, recommendations for fertilization P (SP-36) and K (KCl) are made. The results showed that the obstacle to increasing the productivity of paddy rice in this area is that the content of N, P and K is generally low, and the soil pH ranges from 5-6. Therefore, to increase the productivity of paddy rice yields, it is recommended to apply inorganic fertilizers (N, P, and K) and the addition of organic matter. Based on the results of soil analysis and the nutrient status of paddy soils, site-specific N, P and K fertilization recommendations were obtained. Fertilizers used in the form of Urea, SP-36 and KCl, without the addition of organic matter and with the addition of organic matter.